Slime mould algorithm for practical optimal power flow solutions incorporating stochastic wind power and static VAR compensator device - Kouadri, Ramzi; Slimani, Linda; Bouktir, Tarek (Національний технічний університет "Харківський політехнічний інститут", 2020)
This paper proposesthe application procedure of a new metaheuristic technique in a practical electrical power system to solve optimal power flow problems, this technique namely the slime mould algorithm (SMA) which is inspired bythe swarming behavior and morphology of slime mould innature. This study aims to test and verify the effectiveness of the proposed algorithm to get good solutions for optimal power flowproblems by incorporating stochastic wind power generation and static VAR compensators devices. In this context, different cases are considered in order to minimize the total generation cost, reductionof active power losses as well as improving voltage profile.

У статті пропонується процедура застосування нового метаеврістичного методу в реальній електроенергетичній системі для розв’язання задач оптимального потоку енергії, а саме алгоритму слизової цвілі, який заснований на поведінці рою і морфології слизової цвілі в природі. Дане дослідження спрямоване на тестування і перевірку ефективності запропонованого алгоритму для отримання хороших рішень для проблем оптимального потоку потужності шляхом включення пристроїв стохастичною вітрової генерації і статичних компенсаторів VAR. У зв'язку з цим, розглядаються різні випадки, щоб мінімізувати загальну вартість генерації, знизити втрати активної потужності і поліпшити профіль напруги.
Keywords: stochastic wind power generation; стохастична генерація енергії вітру